Moving Beyond the Nation State? Reflections on European Environmental History. (1st January 2013) - Kalb, Martin
Abstract : This historiographical essay outlines and discusses major trends within European environmental history. More precisely, it traces recent developments and conversations within various national and regional contexts, hoping to provide a coherent overview. In no way comprehensive and complete given the mere scope of the topic, language barriers, and accessibility of materials, the objective of this essay is to capture recent developments and inclinations within a diverse and very complex scholarship. The importance of nature, wilderness, forests, water, political movements, and numerous other themes are discussed in this context, as the essay focuses on different nation states and regions. It highlights recent discussions and future possibilities regarding collaboration across national borders and contexts, and ultimately argues for more transnational cooperation within the field of environmental history.